THE IMPACT OF OVERSEAS CSR IMPLEMENTATION ON LIFTING PERFORMANCE AND CORPORATE PROFITABILITY AT PERTAMINA INTERNATIONAL EP: A SEM-PLS APPROACH - Nurul Intan Permanasari; Andi Mardhotilla; Jerry Heikal (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This study investigates the effect of overseas Corporate Social Responsibility (CSR) on two performance outcomes of Pertamina International EP (PIEP): lifting (Y1) and corporate profit (Y2). Using a quantitative, explanatory design, we compiled 32 observations from four operating areas (Malaysia, Iraq, Algeria, HQ-International) across 2018–2025. CSR is modeled as a latent construct (X) with three reflective indicators CSR_Education, CSR_Environment, and CSR_Overseas while Y1 is measured by lifting_bpd and lifting efficiency, and Y2 by revenue and net profit. Data were analyzed with SEM-PLS (SmartPLS 4). The measurement model meets all thresholds (outer loadings ≥0.70; AVE ≥0.50; CR and Cronbach’s alpha ≥0.70), with particularly strong reliability for CSR (CR=0.986; AVE=0.973) and Profit (CR=0.978; AVE=0.978). The structural model shows CSR has a positive and significant effect on both outcomes: CSR → Lifting (β=0.92; t=59.816; p<0.001; R²=0.847; Q²=0.515) and CSR → Profit (β=0.961; t=80.605; p<0.001; R²=0.924; Q²=0.898). Among indicators, CSR_Overseas (λ=0.988) is the strongest signal within the CSR construct; lifting_bpd (λ=0.935) dominates Y1; and revenue and net profit (both λ=0.989) equally anchor Y2. The findings imply that targeted, context-sensitive overseas CSR can simultaneously stabilize operations and strengthen financial outcomes in international upstream oil and gas.